2021
DOI: 10.1161/jaha.120.018097
|View full text |Cite
|
Sign up to set email alerts
|

AdipoRon Attenuates Inflammation and Impairment of Cardiac Function Associated With Cardiopulmonary Bypass–Induced Systemic Inflammatory Response Syndrome

Abstract: Background Cardiac surgery using cardiopulmonary bypass (CPB) frequently provokes a systemic inflammatory response syndrome, which is triggered by TLR4 (Toll‐like receptor 4) and TNF‐α (tumor necrosis factor α) signaling. Here, we investigated whether the adiponectin receptor 1 and 2 agonist AdipoRon modulates CPB‐induced inflammation and cardiac dysfunction. Methods and Results Rats underwent CPB with deep hypothermic circulatory arrest … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 29 publications
0
17
0
Order By: Relevance
“…Targeting CTRP1 may be used as a therapeutic management to treat cardiac dysfunction post MI [ 84 ]. In the rat model, AdipoRon (an adiponectin receptor) was found to decrease inflammation and weaken heart functions caused by CPB through mediation of AMPK that upregulates immunosuppressive IL-10 and inhibits proinflammatory cytokines like TLR4 and TNF-α in cardiac cells [ 85 ]. Mesenchymal stem cells have been used therapeutically in mice for pressure overload-led heart failure, which involved the existence of plasma adiponectin and T-cadherin expression as well as biogenesis of exosome in the treated mesenchymal stem cells with a high level of exosomes in plasma.…”
Section: Significant Cellular Roles Of Adiponectin As a Rescue Hormon...mentioning
confidence: 99%
“…Targeting CTRP1 may be used as a therapeutic management to treat cardiac dysfunction post MI [ 84 ]. In the rat model, AdipoRon (an adiponectin receptor) was found to decrease inflammation and weaken heart functions caused by CPB through mediation of AMPK that upregulates immunosuppressive IL-10 and inhibits proinflammatory cytokines like TLR4 and TNF-α in cardiac cells [ 85 ]. Mesenchymal stem cells have been used therapeutically in mice for pressure overload-led heart failure, which involved the existence of plasma adiponectin and T-cadherin expression as well as biogenesis of exosome in the treated mesenchymal stem cells with a high level of exosomes in plasma.…”
Section: Significant Cellular Roles Of Adiponectin As a Rescue Hormon...mentioning
confidence: 99%
“…In the liver, AdipoRon attenuated carbon tetrachloride-induced liver damage by inhibiting the expression of proinflammatory cytokines and activation of hepatic stellate cells [ 14 ]. In the heart, AdipoRon relieved cardiopulmonary bypass-induced cardiac inflammation and functional impairment by inhibiting TLR4/TNF- α signaling in cardiomyocytes [ 13 ]. Therefore, these results suggest that AdipoRon alleviates mechanical nociception in SNI mice by inhibiting TNF- α expression in the spinal cord.…”
Section: Discussionmentioning
confidence: 99%
“…Importantly, AdipoRon attenuated postischemic myocardial apoptosis through both AMPK-mediated and AMPK-independent signaling. In another study, Jenke et al [ 36 ] showed that AdipoRon reduces inflammation and impairment of cardiac function associated to systemic inflammatory response syndrome induced by cardiopulmonary bypass (CPB) in rats. Oral gavage of AdipoRon resulted in activation of AMPK and reduction in CPB-upregulation of TNF-α and IL-β as well as NADPH oxidase and inducible nitric oxide synthase (iNOS) [ 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…In another study, Jenke et al [ 36 ] showed that AdipoRon reduces inflammation and impairment of cardiac function associated to systemic inflammatory response syndrome induced by cardiopulmonary bypass (CPB) in rats. Oral gavage of AdipoRon resulted in activation of AMPK and reduction in CPB-upregulation of TNF-α and IL-β as well as NADPH oxidase and inducible nitric oxide synthase (iNOS) [ 36 ]. Gu et al [ 37 ] demonstrated that AdipoRon protects against contrast-induced nephropathy by suppressing oxidative stress and inflammation by activation of the AMPK pathway.…”
Section: Discussionmentioning
confidence: 99%